AN EXPLORATORY SEQUENTIAL SENTIMENT ANALYSIS OF ONLINE LEARNING DURING THE MOVEMENT CONTROL ORDER IN MALAYSIA - Noorihan Abdul Rahman; Zuriani Ahmad Zukarnain; Nor Asma Mohd Zain; Rozianiwati Yusof (UUM Press, 2021)
Purpose - Online learning is an essential platform to support varying learning conditions, anytime and anywhere. It helps connect online communities regardless of one's geographical location and time zone. During the COVID-19 outbreak in Malaysia, the use of online learning platforms has become a crucial option for accomplishing learning objectives. During this challenging time, universities have been looking for suitable solutions to address issues regarding the online learning process. This paper discusses the challenges in online learning, as well as the importance of collaborative learning activities during the Movement Control Order (MCO). Challenges in emotion and changes of routine among students have been detected during the MCO imposed by the government of Malaysia.   Methodology - An exploratory sequential approach was carried out in this study to obtain students' feedback in terms of their emotions and routine changes during the outbreak of COVID-19 and the subsequent implementation of the MCO. Convenience sampling was used for this research, and in order to obtain feedback on online learning during the MCO an online interview was conducted with 42 students from the Faculty of Computer and Mathematical Sciences, Universiti Teknologi MARA branch in the state of Kelantan. The feedback items were recorded and transcribed in Excel format. Next, sentiment analysis was carried out using Rapidminer software.   Findings - The results showed that higher education institutions or universities had to play their part in providing a virtual learning environment as convenient as possible during the Movement Control Order period. The results also showed that educators had to ensure the success of online learning by maintaining the motivation of their students   Significance - The findings in this study can also benefit educators and higher education institutions or universities in executing suitable teaching and learning plans during the COVID-19 outbreak.